Стадії розвитку організації - Нинюк, М.; Nynyuk, М. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
В статті розкрито сутність організації як первинної функції управління та особливості її розвитку, що залежить від професіоналізму управлінських кадрів. Розкрито різні підходи до визначення суті життєвого циклу організації. Визначено, що життєвий цикл організації - це сукупність стадій, що створюють закінчене коло розвитку протягом певного проміжку еволюції організації, після якого його цінності й напрями можуть принципово змінюватися. Тому, життєдіяльність організації від моменту створення і до ліквідації може бути циклічним спіралеподібним процесом. The article reveals the essence of the organization as the primary management functions and features of its development, which depends on the professionalism of the administration. Different approaches to determination of the essence of the life cycle of the organization are revealed. It’s determined that the life cycle of the organization – is the set of stages that create a complete circle of development within a certain period of the evolution of the organization, after which its values and directions can be fundamentally changed. That’s why the activity of the organization from the inception to the liquidation can be cyclic and spiral process. The model of the organization’s lifecycle can serve as an important and effective tool of its diagnostics, facilitating elimination of current problems and enabling the executive bodies and local self-government to perform the strategic transformation in time to ensure a continuous development of organizations.
Stages of the Organization’s Development
Keywords: організація; категорія управління; функція управління; професіоналізм; державне управління; organization; category of management; function of administration; professionalism; public administration